Measurement of turbid media by total internal reflection with Goos-Hänchen angle displacement - Yang Miao; ChenJun Dong; Yufeng Ma; Chenghao Jia; Zeng Wang; Haibin Liu (Results in Physics)
Based on the Goos-Hänchen effect and the intensity attenuation of the evanescent wave penetrating and traveling, a new theoretical model of total internal reflection from the interface of turbid media is proposed and an analytical reflectance expression in a wide incident angle range is developed. The Goos-Hänchen angle displacement between the critical reflectance and the saturated reflectance is discovered. A sensor, for measuring the complex refractive index of turbid media in real-time, with divergent light source is designed. The captured images show that the light distribution reflected from the transparent medium has a sharp boundary, but for turbid media, the reflected light intensity attenuates during the transition from total to non-total internal reflection regions. It is successful and accurate that the new model fits the experimental data of the reflectance and the complex refractive index of turbid media is measured by our sensor. The results show that measuring has advantages in real-time, in situ, and with high accuracy.